Real-time hierarchical predictive risk assessment at the national level: Mutually agreed predicted service disruption profiles - Malinowski, Krzysztof (1948- ); Karbowski, Andrzej (Zielona Góra: Uniwersytet Zielonogórski)
We present a real-time hierarchical approach to an on-line risk assessment at the national level taking into account both local risk analyses performed by key service operators and relevant interdependencies between those services. For this purpose we define mutually agreed predicted service disruption profiles and then propose a coordination mechanism to align those profiles. A simple, four-entity example is provided to illustrate the coordination.
Keywords: risk assessment; cyber security; hierarchical approach; service disruption profiles; coordination